Ekstra adrenal yerleşimli dev feokromositoma - (:unkn) unknown (My University, 2012)
Feokromositoma, adrenal medullanın kromafin hücrelerinden köken alan, katekolamin salgılayan bir tümördür. Feokromositoma çocuklarda %35, erişkinlerde ise %10 oranında adrenal gland dışında yerleşir. Bu çalışmada, infrarenal yerleşim gösteren bir feokromositoma olgusuna tanı ve tedavi yaklaşımımız değerlendirilmiştir.

Pheochromocytoma is a catecholamine secreting tumor originating from the chromaffin cells of the adrenal medulla. The tumor can be located in extra-adrenal tissue with a ratio of 35% in children, and 10% in adults. This study reviews our diagnosis and treatment strategy in a case of infrarenal pheochromocytoma.
Extra-adrenal giant pheochromocytoma
Keywords: Endokrinoloji ve Metabolizma